NOKEN ELECTORAL SYSTEM IN PAPUA DELIBERATIVE DEMOCRACY IN PAPUAN TRADITION - Cahyo Pamungkas (LIPI Press, 2017)
Studies of the noken system from the legal approach have been thoroughly investigated, particularly in the 2009 and 2014 elections and the 2014 presidential election in Papua. Several studies of state’s law explain that the noken system is legitimate according to Indonesian laws due to cultural characteristics of Papuan following Melanesian traditions. Different from those studies, this paper examines the noken system according to Habermas’ theoretical framework of deliberative democracy. This study argues that the noken system is strongly powerful as various cultural communities of native Papuans discuss it. The discussions are discursive practices and contestations to determine political decisions, such as certain political figure or political party to be voted in the election. The essence of the noken system is, therefore, a community's participation via consultations and discussions in deciding political choices collectively. Using literature review, the author discusses the implementation of the noken system in Papua province related to the concept of deliberative democracy. Findings indicate that the implementation of noken system reflects the practices of deliberative democracy, proposed by Habermas, at the village community level. In some cases, however, Papuan elites, who unilaterally decide all votes without any discussions and consent of their community, manipulate the noken system. Theoretically, the noken system shows that democracy is not only legislative procedures, but also an art of maintaining collectivism and social integration. Studi-studi mengenai legalitas penggunaan sistem noken dalam Pemilu 2009 dan 2014 dan pemilihan presiden 2014 di Papua telah banyak dilakukan. Beberapa studi menyatakan bahwa sistem noken tersebut sah dalam sistem hukum Indonesia karena menyesuaikan dengan karakteristik budaya orang Papua yang mengikuti tradisi Melanesia. Berbeda dengan studi tersebut, tulisan ini melihat sistem noken dalam perspektif demokrasi deliberatif Habermas. Studi ini berargumen bahwa sistem noken masih sangat kuat karena banyak didiskusikan oleh berbagai komunitas budaya orang asli Papua. Musyawarah dalam sistem noken merupakan praktik diskursif dan kontestasi untuk menentukan keputusan politik, seperti kandidat atau partai politik dalam Pemilu. Inti sistem noken adalah partisipasi masyarakat melalui konsultasi dan diskusi dalam menentukan pilihan politik secara kolektif. Dengan tinjauan pustaka, artikel ini membahas pelaksanaan sistem noken di Provinsi Papua terkait konsep demokrasi deliberatif. Temuan penelitian menunjukkan bahwa penerapan sistem noken menggambarkan praktik demokrasi deliberatif di tingkat masyarakat desa. Namun, dalam beberapa kasus, sistem noken dimanipulasi oleh elit Papua, yang secara sepihak memutuskan semua suara tanpa adanya diskusi dan persetujuan dari komunitas. Secara teoritis, sistem noken menunjukkan bahwa demokrasi bukan hanya prosedur legislatif, tapi juga seni dalam menjaga kolektivisme dan integrasi sosial.